THE EFFECTIVENESS OF AN INDIVIDUAL APPROACH IN THE PROCESS OF TEACHING FOREIGN LANGUAGES (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article discusses some features of improving the quality of education in teaching foreign languages in universities. The results of the analysis of problems arising in the process of teaching foreign languages are given. Attention is paid to improving the effectiveness of training sessions, through the use of various audio and video materials, with the help of computer technology. The possibilities of the technology of individualized learning, which contributes to increasing the level of foreign language proficiency, are discussed. The main factors on which it is necessary to pay attention to the teacher in the organization of the educational process for teaching a foreign language are proposed.